(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2019)
Response or reaction of the mind to the pressure of life is stress. Medical students of Bangladesh are in stress to meet the demands of the curriculum. This study was conducted on the regularly passed final year students of a medical college to find out the nature of stresses perceived by them. The response was collected on a validated structured set of questionnaire, 3 weeks prior to the University level summative examination and 63 students (33 male and 30 female) participated in the study. Stress was expressed in five levels and scored as 0 to 4. Academic related factors were identified as maximum stress provoking (2.5 ± 1.3) than group activity (1.6 ± 1.4), drive (1.4 ± 1.5), teaching-learning (2.3 ± 1.3), personnel (1.8 ± 1.6) or social (1.9 ± 1.5) related factors. Of that group of stress, ‘falling behind reading schedule’ and ‘large amount of content to be learned’ were revealed as heavy stressors. Examination was identified as a severe stressor in 42.4% male, but was marked less (16.7%) in the female. ‘Too much restriction in the campus’ was observed as heavy stressors among the factors other than the academic related stressors. Students may be motivated to develop a coping strategy for academic and teaching-learning related stress.